Pengaruh Fee Audit, Pergantian Auditor, Dan Ukuran Perusahaan Terhadap Audit Delay - Fathonah, Salsabila; Sari, Ika; Mubarakah, Septyana (Gorontalo Accounting Journal, 2024)
This study aims to test, analyze and obtain empirical evidence regarding the effect ofÂ  fee audit, auditor switching, and company size on audit delay. This research was conducted on mining sector companies listed on the Indonesia Stock Exchange during the 2021-2022 period. This study uses secondary information from financial statements of mining companie listed on the Indonesia Stock Exchange. The sampling technique in this study uses purposive sampling with several predetermined criteria so that the samples obtained were 72 samples. The data analysis method used is panel data regression test use the software application Eviews. The results of this study indicate that (1) Fee Audit has a negative effect on audit delay, (2) Auditor Switching has no effect on audit delay, and (3) Company Size has no effect on audit delay.